The Impact of Cryptocurrency on The Indonesian Community's Economy - Myers, Kiara; Robert Hinman, Christopher (IAIC Bangun Bangsa, 2023)
All industries, including banking, will be impacted by the development of information technology. The creation of cryptocurrency, also known as virtual currency or digital currency, is a result of the advancement of financial technology. On the internet, the usage of digital currencies as a form of payment started to spread. This currency is intended to make payments more convenient and secure. Using blockchain technology, it lowers the cost of transactions. However, because it hurts Indonesia's financial system, monetary stability, and payment system, the government, in this case, Bank Indonesia, forbids transactions using digital or virtual currency. The influence of cryptocurrencies on the Indonesian economy and the government's position on the country's current technology are both explained in this paper. In terms of the technology provided, cryptocurrencies are a development in financial technology that will enable future financial transactions to convert paper money into digital money. To prevent future legislation from outlawing the technology found in cryptocurrencies and to help the general public better comprehend cryptocurrencies, it is desired that the government would examine the technology in cryptocurrencies more thoroughly.